Bike and cycle polo's terminology translation issues from a cognitive linguistics perspective - Shoba (2016)
The purpose of this dissertation is to give a contribution to the translation of the terminology of Cycle and Bike Polo into European Portuguese and hence call the attention of a wide Portuguese public to this fairly new sport, whose roots go back to Elephant and Horse Polo in India and in other parts of the world. Sequencing a characterization of technical translation, translation issues of Bike and Cycle Polo´s terminological units have been dealt with in the light of the Cognitive Linguistics framework and hence intimately associated both with physical experiences and historical facts. In fact, sports terminology coinage in this field is highly motivated by metaphorical and metonymical conceptualization mapped from physical reality dimensions, as well as from already existing sports terminology from other sports modalities. In order to render this research unique, a glossary of technical terms from Bike and Cycle Polo has been gathered, since most of them had not yet undergone translation from English into European Portuguese. For validation of my translations I have resorted to Portuguese bike polo players, with special reference to Catarina Almeida, who introduced me to Bike Polo’s terminology.